IN VITRO ANTIOXIDANT ACTIVITY AND PHYTOCHEMICAL SCREENING OF LEAF EXTRACTS OF GREWIA HETEROTRICHA MAST - USHA, B.; PUSHPALATHA, K. C. (International Journal of Current Pharmaceutical Research, 2016)
Objective: To investigate the presence of phytochemical components and to evaluate the in vitro antioxidant activity of pet. ether, chloroform, methanol and aqueous extracts of Grewia heterotricha mast leaves. Methods: The leaves of Grewia heterotricha mast were dried and extracts were prepared using a pet. ether, chloroform, methanol by soxhlet extraction method. The aqueous extract was prepared using distilled water by cold extraction method. The preliminary phytochemical analysis was carried out on aqueous, methanol, chloroform and pet. either leaf extracts of the plant using standard qualitative procedures. The total phenolic content (TPC) was estimated using modified Folin-Ciocalteau method, tannin content by Folin-Denis method and total flavonoids by aluminum chloride method. In vitro, antioxidant activities were evaluated by 1,1-Diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, H2O2 scavenging activity and FRAP assay. Results: The preliminary phytochemical analysis revealed the presence of complex bioactive constituents like phenols, tannins, alkaloids, terpenoids, flavonoids, saponins, steroids, glycosides, coumarins, proteins and carbohydrates. Methanolic extract showed highest total phenolic content (87.58±2.52 mg CE/g) than aqueous extract (78.46±5.36 mg CE/g). Higher tannin content was found in the aqueous extract (148.0±8.96 mg TAE/g). Total flavonoids were highest in chloroform extract (314.9±25.06 mg QE/g) followed by aqueous (242.98±32.42 mg QE/g) and methanolic extract (217.0±18.32 mg QE/g) and lowest in a pet. ether extract (188.86±23.35 mg QE/g). The methanolic extract had shown very significant DPPH radical scavenging activity (IC50 98.95 µg/ml) and H2O2 scavenging activity (IC50110.1µg/ml) compared to the standard ascorbic acid. Higher reducing ability was observed in methanol extract (131.8±11.67 mg AE/g). Conclusion: The results obtained reveal that the leaves of Grewia heterotricha mast have potent antioxidant property. The observed activity may be associated with bioactive components like phenolics, flavonoids present in the leaf extracts and could have greater importance as therapeutic agents in oxidative stress-related degenerative diseases. Further studies are needed in order to purify bioactive compounds responsible for the antioxidant property.